The Urgency of Bilateral Petroleum Relations Between Indonesia and Saudi Arabia as An Effort to Support Stable Economic Value - Farhan, Muhammad (Abdurrauf Social Science, 2024)
This article reviews the urgency of bilateral relations between Indonesia and Saudi Arabia, where Indonesia with all its capabilities and efforts, bilateral cooperation between Indonesia and Saudi Arabia is very well and smoothly established. However, currently, the decline in Indonesia's economic value continues to be echoed by the people and the nation, which at the same time Indonesia still maintains bilateral economic relations with several countries that can be said to have strong economic power such as Saudi Arabia, for example. This research aims to maintain the economic welfare of our nation so that it continues to be stable without any need to worry about the decline and decline of economic value in this country This article was made using a qualitative method using several research instruments such as reading books, journals and articles related to journal discussions The results are to encourage the nation's leaders as well as Indonesia's economists to compile a draft that systematically and carefully related to the planning of the continuity of cooperation between the two parties so that the bilateral process can be well established, it is also undeniable that the Ministry of Foreign Affairs and the Ministry of Finance of Indonesia also play an important role in this matter in order to maintain Indonesia's economic stability.  Abstrak: Artikel ini mengulas tentang urgensi hubungan bilateral yang terjain antara Indonesia dan Arab Saudi, dimana Indonesia dengan segala kemampuan dan upayanya, kerja sama bilateral antara Indonesia dan Arab Saudi terjalin dengan sangat baik dan lancar. Namun saat ini, kemerosotan nilai ekonomi Indonesia terus digaungkan oleh para rakyat dan bangsanya yang mana dalam waktu yang sama  Indonesia masih menjalin hubungan bilateral Ekonomi dengan beberapa negara yang bisa dibilang memiliki kekuatan ekonomi yang kuat seperti Arab Saudi contohnya. Penelitian ini bertujuan untuk menjaga kesejahteraan ekonomi bangsa kita agar terus stabil tanpa ada perlu rasa khawatir dengan keterpurukan dan kemerosotan nilai ekonomi di negara ini Artikel ini ini dibuat dengan menggunakan metode kualitatif dengan menggunakan beberapa instrumen penelitian seperti  buku bacaan, jurnal  juga artikel artikel yang berkenaan dengan pembahasan jurnal  Adapun hasilnya adalah mendorong para pemimpin bangsa juga para ekonom Indonesia untk menyususn rancangan yang sistematis dan matang terkait perencanaan kelangsungan Kerjasama antara kedua belahpihak sehingga proses bilateral dapat terjalin dengan baik, juga tidak dapat dipungkiri bahwa Kemenlu dan Kemenkeu Indonesia juga berperan penting dalam hal ini demi menjaga kestabilan ekonomi Indonesia.  Keyword: Bilateral, Ekonomi, Arab Saudi, Indonesia, Timur Tengah